2020
DOI: 10.1097/ta.0000000000002671
|View full text |Cite
|
Sign up to set email alerts
|

Heroes in crisis: Trauma centers should be screening for and intervening on posttraumatic stress in our emergency responders

Abstract: BACKGROUND Emergency responders face a crisis of rising suicide rates, and many resist seeking help due to the stigma surrounding mental health. We sought to evaluate the feasibility of an urban trauma center to screen for posttraumatic stress (PTS) among emergency responders and to provide mental health services. METHODS Paramedics, firefighters, law enforcement, and corrections officers involved with patients in the trauma unit were asked to complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…In addition, people who have been exposed to traumatic experiences or adverse experiences can be affected at different levels in relation to factors such as their proximity to the event and the severity of traumatic events (Iz et al, 2019;Lai et al, 2020;May & Wisco, 2016). Previous research indicated that those who struggle in the front line with the first responders are exposed to a more intense stress load (Tatebe et al, 2020). The present study reported that healthcare professionals were affected at a similar level Table 4.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In addition, people who have been exposed to traumatic experiences or adverse experiences can be affected at different levels in relation to factors such as their proximity to the event and the severity of traumatic events (Iz et al, 2019;Lai et al, 2020;May & Wisco, 2016). Previous research indicated that those who struggle in the front line with the first responders are exposed to a more intense stress load (Tatebe et al, 2020). The present study reported that healthcare professionals were affected at a similar level Table 4.…”
Section: Discussionmentioning
confidence: 50%
“…Previous research findings point out that healthcare professionals, especially those working in the frontline are at risk of adverse psychological impact during the pandemic ((Tatebe et al, 2020;Wu et al, 2009). Quarantine and other pandemics related factors such as death of a relative or friend due to the disease or exposure to media images and news about the epidemic may also have adverse effect on mental wellbeing of healthcare professionals (WHO, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…40,41 It is essential for our specialty to establish a mechanism by which health care workers have early access to confidential, professional behavioral health resources for further support during this crisis. 42 Digital and technologic platforms are an important adjunct to typical behavioral support, especially given the unique challenges of social distancing. Some mobile applications may provide support in a more informal manner.…”
Section: Similarities To and Differences From Previous Pandemicsmentioning
confidence: 99%
“…During the COVID-19 pandemic, they worked in emergency services with innovative solutions by synthesizing up- to-date information about COVID-19 infection while ensuring the survival of their patients. Using professional behavioural health resources with mechanisms that can be accessed at an early stage to emergency medicine professionals and other healthcare professionals during the pandemic process may reduce their anxiety level [31,32].…”
Section: (Sd) Medianx (Sd) Medianmentioning
confidence: 99%